Tripterygium hypoglaucum (Lévl.) Hutch and Its Main Bioactive Components: Recent Advances in Pharmacological Activity, Pharmacokinetics and Potential Toxicity - Junqi Zhao; Fangling Zhang; Xiaolin Xiao; Zhao Wu; Qichao Hu; Yinxiao Jiang; Wenwen Zhang; Shizhang Wei; Xiao Ma; Xiaomei Zhang (Frontiers in Pharmacology, 2021)
Tripterygium hypoglaucum (Lévl.) Hutch (THH) is believed to play an important role in health care and disease treatment according to traditional Chinese medicine. Moreover, it is also the representative of medicine with both significant efficacy and potential toxicity. This characteristic causes THH hard for embracing and fearing. In order to verify its prospect for clinic, a wide variety of studies were carried out in the most recent years. However, there has not been any review about THH yet. Therefore, this review summarized its characteristic of components, pharmacological effect, pharmacokinetics and toxicity to comprehensively shed light on the potential clinical application. More than 120 secondary metabolites including terpenoids, alkaloids, glycosides, sugars, organic acids, oleanolic acid, polysaccharides and other components were found in THH based on phytochemical research. All these components might be the pharmacological bases for immunosuppression, anti-inflammatory and anti-tumour effect. In addition, recent studies found that THH and its bioactive compounds also demonstrated remarkable effect on obesity, insulin resistance, fertility and infection of virus. The main mechanism seemed to be closely related to regulation the balance of immune, inflammation, apoptosis and so on in various disease. Furthermore, the study of pharmacokinetics revealed quick elimination of the main component triptolide. The feature of celastrol was also investigated by several models. Finally, the side effect of THH was thought to be the key for its limitation in clinical application. A series of reports indicated that multiple organs or systems including liver, kidney and genital system were involved in the toxicity. Its potential serious problem in liver was paid specific attention in recent years. In summary, considering the significant effect and potential toxicity of THH as well as its components, the combined medication to inhibit the toxicity, maintain effect might be a promising method for clinical conversion. Modern advanced technology such as structure optimization might be another way to reach the efficacy and safety. Thus, THH is still a crucial plant which remains for further investigation.